(3ebGeI GdShjOis - (3YHO Gddg Hf MSjf Hf eQYj Hf fGUQ GdOjf GdHZOGOj, CHh GdHQcGJ GdShjOj,J (B1174 (3g` s ((3YHOGddg Hf YjSi Hf ESeGYjd s)
(3ChdgG (B:s
(3CeG HYO , abGd GdTjN YHOGddg GdShjOi(B: (3hCjGe cfG ai OeTb s
(3BNQgG (B:s
(3EdG agh eYRhd HMce TQY Gdghi hedJg, hGSJZaQ Gddg ef GdJLhR ai GdebGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B48s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B94 s
Keywords: (3GdCOHs